PO 8372 Culture-free approaches for the diagnosis and management of patients with rifampicin resistant tuberculosis: the DIAMA project. (24th April 2019) - Massou, Faridath; Affolabi, Dissou; Merle, Corinne; Abebe, Gemeda; Bah Sow, Oumou; Diarra, Bassirou; El Tayeb, Osman; Gaye Diallo, Ayou; Kaswa, Michel; Claude Ngabonziza Semuto, Jean; Sander, Melissa; Supply, Philip; et al.
Abstract : Background: Recent advances in molecular diagnostics, especially the Xpert MTB/Rif test, have reduced the time to diagnose rifampicin resistant tuberculosis (RR-TB). However, with this test only rifampicin resistance is diagnosed, leading to presumptive diagnosis of resistance to isoniazid and maybe other drugs. In addition, culture on monthly sputum samples is currently recommended by the World Health Organization (WHO) for follow-up of RR-TB patients under treatment. Unfortunately, culture is often not locally available, and samples need to be shipped from field to culture laboratories. The associated transport delays lead to high rates of contamination and false-negative culture, particularly in laboratories in low-resource settings. Many gaps for the diagnosis and management of RR-TB patients still need to be addressed and the DIAMA project (Diagnostics for multidrug-resistant tuberculosis in Africa) aims to address some of them. Methods: The TB Supranational Reference Laboratory of Benin leads a consortium of 11 partners involved in multiple-drug resistant TB care in Africa. The DIAMA project will explore the feasibility and accuracy of: i) diagnosing TB resistance to first and second line drugs through novel molecular multiplex assays developed by the company Genoscreen; ii) setting-up alternative culture-free approaches for the monitoring of patients' response to rifamipcin-resistant treatment; iii) piloting whether the implementation of software by Data2Care Technologies for real-time monitoring of molecular test results can reduce delays between diagnosis and treatment of RR-TB patients. This project is funded by EDCTP for a period of five years. Conclusion: Together, these advances could dramatically improve the currently dismal prognosis of multiple-drug resistant TB in health systems in resource-poor settings. Through this presentation, we will share the background information, the design of this project and its progress.